High Viscosity Oil Development Technology - V.P. Ovchinnikov; O.V. Rozhkova; P.V. Ovchinnikov; O.N. Shemelina (International Journal of Petroleum Technology, 2019)
The development of hard-to-recover reserves is now becoming a prerequisite for a successful oil business. Nevertheless, there is still no consensus on what reserves should be classified in this category and what benefits should be received by oil industry workers during their development. At the same time, it is the improvement of the tax system that can spur the development of new technologies for the extraction of “complex” oil and ensure the profitability of its production.